CHARACTERIZATION AND CLUSTERING OF SOME GUAVA GERMPLASM COLLECTIONS BASED ON LEAF AND FRUIT CHARACTERS - Nasution, Fitriana; Hadiati, Sri (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
Guava has several different accessions. Guava diversity needs to be studied and evaluated in order to determine the next steps in the guava breeding. The objective of this research was to characterize and cluster of some guava germplasm collections. The study was conducted at Aripan and Subang experimental farm, Indonesian Tropical Fruit Research Institute from January 2012 to December 2012. Five fruits of each accession were randomly selected sampled and then characterized using UPOV guidelines. Obtained data were analyzed by NTSYS ver.2.1. The Similarity level of 19 accessions ranged from 70 â 90% or the genetic distance was between 0-20%. Dendogram obtained could be clustered into two different groups, namely group I (ARP9406, ARP9407, ARP8653, ARP8742, ARP10.2, JBT001, JBT002, ARP8740, JBT003 and JBT004), group II (ARP10.7, ARP10.6, ARP10.1, ARP10.12, ARP10.9, ARP10.11, ARP8744, ARP8741 and ARP8743). The result of this research can be used for guava breeding. Species diversity and genetic resources are very important to get new varieties. This study would be highly valuable in the future.Â Keywords :Â GuavaÂ Germplasm, Characterization, Clustering